Mechanistic insights on anserine hydrolyzing activities of human carnosinases - Pandya, Vaibhav Kumar; Shankar, S. Shiva; Sonwane, Babasaheb P.; Rajesh, S.; Rathore, Rajeshwari; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (Biochimica et biophysica acta. General subjects, 2023)
Anserine and carnosine represent histidine-containing dipeptides that exert a pluripotent protective effect on human physiology. Anserine is known to protect against oxidative stress in diabetes and cardiovascular diseases. Human carnosinases (CN1 and CN2) are dipeptidases involved in the homeostasis of carnosine. In poikilothermic vertebrates, the anserinase enzyme is responsible for hydrolyzing anserine. However, there is no specific anserine hydrolyzing enzyme present in humans. In this study, we have systematically investigated the anserine hydrolyzing activity of human CN1 and CN2. A targeted multiple reaction monitoring (MRM) based approach was employed for studying the enzyme kinetics of CN1 and CN2 using carnosine and anserine as substrates. Surprisingly, both CN1 and CN2 can hydrolyze anserine effectively. The observed catalytic turnover rate (Vmax/[E]t) was 21.6 s−1 and 2.8 s−1 for CN1 and CN2, respectively. CN1 is almost eight-fold more efficient in hydrolyzing anserine compared to CN2, which is comparable to the efficiency of the carnosine hydrolyzing activity of CN2. The Michaelis constant (Km) value for CN1 (1.96 mM) is almost three-fold lower compared to CN2 (6.33 mM), representing higher substrate affinity for anserine-CN1 interactions. Molecular docking studies showed that anserine binds at the catalytic site of the carnosinases with an affinity similar to carnosine. Overall, the present study elucidated the inherent promiscuity of human carnosinases in hydrolyzing anserine using a sensitive LC-MS/MS approach. •Employed sensitive LC-MS/MS approach to study anserine hydrolyzing activities of human carnosinases (CN1 and CN2).•First report on detailed kinetic characterization of anserinase activity of human CN1 and CN2.•Dissecting the molecular interactions involved in anserine-CN1 and anserine-CN2 binding using molecular docking approach.